THE USE OF PEDAGOGICAL TECHNOLOGIES IN THE LESSONS OF MUSIC THEORY - Fozilov Qahramon Madaminovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The purpose of teaching the educational science” music theory "is to educate conscious thinking in relation to musical expressiveness and form the ability to perceive it, to form and develop students' vision, and perception of the musical world, to correctly direct and enrich their musical-aesthetic taste, to cultivate their creative abilities; to prepare students for practical activities as a music teacher.